Physicochemical surface-structure studies of highly active zirconocene polymerisation catalysts on solid polymethylaluminoxane activating supports. (11th September 2020) - Kilpatrick, Alexander F. R.; Rees, Nicholas H.; Turner, Zoë R.; Buffet, Jean-Charles; O'Hare, Dermot
Abstract : Static 91 Zr ssNMR, SEM-EDX, and DRIFT spectroscopy indicate that a common zirconium species, [Cp R 2 ZrMe] +, is present in all sMAO supported catalyst systems. Abstract : Physicochemical surface-structure studies of highly active slurry-phase ethylene polymerisation catalysts has been performed. Zirconocene complexes immobilised on solid polymethylaluminoxane (sMAO) (sMAO–Cp2 ZrX2 ), have been investigated using SEM-EDX, diffuse reflectance FT-IR (DRIFT) and high field (21.1 T) solid state NMR (ssNMR) spectroscopy. The data suggest a common surface-bound cationic methylzirconocene is the catalytically active species. 91 Zr solid sate NMR spectra of sMAO–Cp2 ZrCl2 and sMAO–Cp2 ZrMe2 are consistent with a common surface-bound Zr environment. However, variation of the σ-donor (X) groups on the metallocene precatalyst leads to significant differences in polymerisation activity. We report evidence for X group transfer from the precatalyst complex onto the surface of the aluminoxane support, which in the case of X = C6 F5, results in a 38% increase in activity.